Analisis Terhadap Cryptocurrency (Perspektif Mata Uang, Hukum, Ekonomi Dan Syariah) - Afrizal Afrizal; Marliyah Marliyah; Fuadi Fuadi (Faculty of Economics and Business, Universitas Malikussaleh, 2021)
The purpose of this study is to analyze cryptocurrencies based on the characteristics of money, legal perspective, economic perspective and sharia perspective. In this study, the methodology used is descriptive with a qualitative approach. The results show that in this case cryptocurrency can be accepted as money (from the perspective of money characteristics), cryptocurrency does not meet the criteria as a currency (currency perspective), cryptocurrency does not fully fulfill the function of currency (economic perspective), cryptocurrency is not a legal currency in Indonesia. (legal perspective) and the existence of two scholars' opinions (accept and prohibit) regarding cryptocurrency (sharia perspective)